Intrinsic alignments of galaxies in the Horizon-AGN cosmological hydrodynamical simulation - Chisari, N; Codis, S; Laigle, C; Dubois, Y; Pichon, C; Devriendt, J; Slyz, A; Miller, L; Gavazzi, R; Benabed, K (Oxford University Press, 2015)
The intrinsic alignments of galaxies are recognised as a contaminant to weak gravitational lensing measurements. In this work, we study the alignment of galaxy shapes and spins at low redshift ($z\sim 0.5$) in Horizon-AGN, an adaptive-mesh-refinement hydrodynamical cosmological simulation box of 100 Mpc/h a side with AGN feedback implementation. We find that spheroidal galaxies in the simulation show a tendency to be aligned radially towards over-densities in the dark matter density field and other spheroidals. This trend is in agreement with observations, but the amplitude of the signal depends strongly on how shapes are measured and how galaxies are selected in the simulation. Disc galaxies show a tendency to be oriented tangentially around spheroidals in three-dimensions. While this signal seems suppressed in projection, this does not guarantee that disc alignments can be safely ignored in future weak lensing surveys. The shape alignments of luminous galaxies in Horizon-AGN are in agreement with observations and other simulation works, but we find less alignment for lower luminosity populations. We also characterize the systematics of galaxy shapes in the simulation and show that they can be safely neglected when measuring the correlation of the density field and galaxy ellipticities.